Infant temperament and childhood psychiatric disorder: longitudinal study - Sayal Heron, K.; Heron, J.; Maughan, B.; Rowe, R.; Ramchandani, P. (Wiley, 2013)
Abstract BACKGROUND: Temperamental characteristics emerge early in life and can shape children's development, adjustment and behaviour. We aimed to investigate the association between early infant temperament and later childhood psychiatric disorder in a community sample. METHODS: This prospective, population-based study used data from the Avon Longitudinal Study of Parents and Children (ALSPAC). In a sample of 7318 children, we investigated whether temperamental characteristics assessed at the ages of 6 months and 24 months are associated with an independent diagnosis of psychiatric disorder ascertained at age 7 years. RESULTS: After adjusting for confounders, temperamental characteristics assessed at 6 and 24 months of age were associated with psychiatric disorder at age 7 years. In particular, intensity of emotional reaction at age 6 months was associated with later disorder (adjusted odds ratio = 1.56; 95% confidence interval 1.19, 2.04; P = 0.002). These associations were stronger in girls and in those children with high levels of intensity at both 6 and 24 months of age. CONCLUSIONS: Temperamental characteristics involving high levels of emotional intensity within the first year of life are longitudinally associated with psychiatric disorder in mid-childhood, suggesting that the roots of psychiatric disorder may, in some cases, lie very early in life.